Kodifikasi Al–Qur’an dan Hadist pada masa Dinasti Umayyah - Salsabilla, Putri Yulia (Maliki Interdisciplinary Journal, 2024)
The results of this writing are utilized to examine the codification of the Qur’an and Hadith during the Umayyad Caliphate. This discourse emerges from inquiries and concerns regarding the integrity and authenticity of the Qur’an manuscript and the miraculous nature bestowed upon Prophet Muhammad (PBUH). Numerous reading errors occurred as the Qur’an reached non-Arabic. Consequently, governmental policies were implemented to codify the Qur’an, aiming to prevent misinterpretations of its meanings. This was particularly evident during the Umayyad Caliphate under the rule of several caliphs. The prevalent misreadings prompted measures to safeguard the accurate transmission of the Qur’an. Policies enacted during the Umayyad dynasty aimed at codifying the Qur’an were designed not to alter its content but to prevent misinterpretations. The mysteries embedded within the Qur’an itself constitute a miraculous aspect still debated by some factions. There is a perception among certain groups that the text of the Qur’an has undergone alterations. However, during the Umayyad Caliphate, numerous manuscripts of Qur’anic writings were discovered, indicating a codification process aimed at preventing reading errors rather than altering the core content of the Qur’an.